Pemikiran Imam Nawawi Tentang Adab dan Relevansinya dengan Kode Etik Guru di Indonesia - Alfath Julfi; Rehani (Universitas Muhammadiyah Prof Dr Hamka, 2023)
This research is motivated by unscrupulous teachers who do not behave in accordance with existing provisions. Imam Nawawi as one of the figures poured his ideas into the book Adabul 'alim Wal Muta'allim. The book contains six points of education which indirectly reveal the adab that a teacher and student must have. This study aims to find out how the teacher's etiquette towards himself, the teacher's etiquette in teaching in the book Adabul 'alim wal Muta'allim and its relevance to the code of ethics for teachers in Indonesia. This type of research is library research with data collection techniques for collecting documents in the form of books, notes and journals that discuss the thoughts of Imam Nawawi and the etiquette of teachers in Indonesia. Based on the research conducted, it is known that Imam Nawawi's thoughts about teacher etiquette are not expressed directly about the teacher's code of ethics but only contain explanations about education. The teacher's code of ethics according to Imam Nawawi which is discussed in this study, namely: first, the teacher's etiquette towards himself. Second, the teacher's manners in teaching. After examining the teacher's etiquette, according to Imam Nawawi's thoughts in the book Adabul 'alim wal Muta'allim, it has similarities with the teacher's code of ethics in Indonesia. Textually the words are not the same, but substantially they are similar. According to Imam Nawawi, the concept of teacher etiquette is more religious than the Indonesian code of ethics. The Indonesian teacher's code of ethics is indeed not based on Islam but still uses religious terms, so that teacher etiquette according to Imam Nawawi does not contradict the Indonesian teacher's code of ethics.